Viscous inertial mass damper (VIMD) for seismic responses control of the coupled adjacent buildings. (15th April 2021) - Lu, Lei; Xu, Jiaqi; Zhou, Ying; Lu, Wensheng; Spencer, Billie F.
Highlights: Use VIMD as equivalent negative stiffness dampers into coupled high-rise buildings. Derive the optimal damper configuration for VIMD by stochastic optimization. Analyze the mechanism of VIMD in the coupled adjacent building system. Recommended VIMD implementation is for sky bridge with bearings. Abstract: Many research studies have focused on a novel kind of damper involved with an inertial/gyro mass component, called the inertial mass damper (IMD). Different realizations of the IMD share common standard features: a sizeable apparent mass and the pseudo-negative dynamic stiffness. The connected control method (CCM) has been proven effective for mitigating vibration between adjacent flexible structures. This paper explores the efficacy of using an IMD in parallel with a viscous damper (termed VIMD) configured in the sky bridge to control the vibration of two adjacent towers under random earthquake excitation. First, numerical models of two buildings are developed using a Timoshenko beam model, which can accommodate both bending and shear deformation. Key damper parameters are explored through a parametric study. Then, stochastic optimization is performed to determine optimum damper parameters and the most effective configuration. The optimization results are analyzed in detail, and guidelines for the damper configuration are recommended. By comparing the optimal control performance between the VIMD and traditional viscous damper (VD), the following conclusions can be drawn: due to its pseudo-negative stiffness characteristics and large damper force, the VIMD can achieve better control performances for a wide range of the axial stiffness of the sky bridge; the VIMD requires a smaller damping coefficient and axial stiffness, which can result in smaller damper sizes and member sections of the sky bridge. Therefore, the VIMD is demonstrated to be a useful alternative for engineering practice in CCM vibration mitigation strategies.